Tajwid, Gramatika Bahasa Arab, dan Adaptasi Kebiasan Baru dalam Peribadatan Sehari-Hari - Aminah, Siti; Hasanah, Uswatun; Wicaksono, Imam (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2021)
The Covid-19 pandemic has brought a new life order which is commonly known as a health protocol implementation. Efforts to deal with the Covid-19 pandemic can be made physically or spiritually. Physical efforts are carried out by applying health protocols in a disciplined manner, while spiritual efforts are carried out by increasing the quality of worship of God. These two efforts must be combined with maintaining the quality of worship in health protocols. In this case, the quality of worship can be improved by deepening the understanding and application of Arabic tajwid and grammar in reciting verse and prayer recitations. In addition, it is necessary to practice morning and evening prayers as self-protection and maintain mental stability. To achieve this goal, this team carried out a community service by compiling two pocketbooks. The first one is related to the application of health protocols in daily worship and another pocketbook containing tajwid material and morning prayer, which was equipped with exposure and training on recitation and reading the morning prayer and evening prayers. These exposures are presented in outreach videos and tutorials. The result shows that people are increasingly aware of implementing health protocols in their daily activities, especially in Islamic worship. In addition, the community's mentality has become more robust, and people have become calmer in living their lives during the pandemic since some people have practiced morning and evening prayers. In addition, they also apply tajwid and Arabic grammar in a better way so that their worship activities become much more solemn. ===== Pandemi Covid-19 membawa manusia kepada tatanan kehidupan baru dengan menerapkan protokol kesehatan. Salah satu hal yang dapat dilakukan dalam mengahadapi pandemi Covid-19 dan terhindar dari penularan virus dapat dilakukan secara jasmani maupu rohani. Upaya jasmaniah dilakukan dengan menerapkan protokol kesehatan secara disiplin, sedangkan upaya rohani dilakukan dengan mendekatkan diri kepada Tuhan dengan meningkatkan kualitas peribadatan. Hal tersebut dapat dilakukan dengan tetap melakukan ibadah dengan menerapkan protokol kesehatan, diikuti dengan pemahaman dan penerapan tajwid dan gramatika Arab dengan benar dalam melafalkan bacaan ayat dan doa. Selain itu, diperlukan pula pengamalan doa pagi dan petang untuk menjaga diri dan meningkatkan kesehatan mental. Untuk mencapai tujuan tersebut, tim melaksanakan pengabdian dengan menyusun buku saku penerapan protokol kesehatan dalam peribadatan sehari-hari dan buku saku yang berisi materi tajwid dan doa pagi-petang yang diikuti dengan penyuluhan dan pelatihan penerapan tajwid dan membaca doa pagi dan petang yang dilakukan dengan membuat video penyuluhan dan tutorial. Hal ini menunjukkan hasil bahwa masyarakat semakin sadar untuk menerapkan protokol kesehatan dalam setiap aktivitas sehari-hari, khususnya dalam peribadatan Islam. Selain itu, mental masyarakat menjadi semakin kuat dan masyarakat menjadi lebih tenang dalam menjalani kehidupan selama pandemi. Hal ini karena sebagian masyarakat telah mengamalkan doa pagi dan petang, serta menerapkan tajwid dan gramatika Arab dengan lebih baik sehingga aktivitas ibadah mereka menjadi semakin khusyu’.